Analisis Faktor Penghambat Implementasi Waste Framework Directive di Campania, Italia - Audrey Rachalia Achmad; Ika Riswanti Putranti; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2017)
In 2007-2013, European Commission (EC) sent three warning letters to the Italian Government for its failure to fulfill its obligation under the Waste Framework Directives (WFD) 2006 (article 4 and 5). EC was concerned with the ongoing waste problem in Campania Region, Italy that had been happening since 1994. To some extent, the problem caused some environmental issues in Campania Region, which was deemed as the exact opposite of what is regulated in the WFD, particularly regarding the implementation of adequate waste management system and the implementation of waste management without endangering the environment and people’s health. This research aims to explain the waste problem in Campania within the period of 2007-2013, and analyzing the factors that prevent the correct implementation of WFD and its implication on the waste problem. The theoritical framework in this research is, Conceptualizing The Domestic Impact of Europe by Tanja A. Börzel and Thomas Risse is being used to analyze those factors. This research uses the qualitative method. This research finds out that the most significant factor that prevented the correct implementation of WFD in Campania was the lack of role of its formal institution, which was the Committee on Waste Emergency (CWE) during 1994-2009. Eventually, those problems during the 15 years of CWE leadership was not easy to be solved within only four years (2010-2013).